Eating disorders and health literacy in Germany: results from two representative samples of adolescents and adults - König, Lars; Schröder, Rebekka; Hamer, Tim; Suhr, Ralf (Frontiers in Psychology, 2024)
Eating disorders are associated with substantial burden for the affected individuals including negative health outcomes and increased mortality. So far, prevention programs for eating disorders have yielded mixed results concerning their efficacy. Therefore, more targeted prevention programs need to be developed. Health literacy has been identified as a potential influencing factor of eating disorders. This study aimed at exploring the relationship between likely cases of eating disorders and health literacy, alongside additional sociodemographic factors. Two large samples of adults (N=3011) and adolescents (N=1021) representative of the German-speaking population in Germany were recruited. Likely cases of eating disorders were identified using the SCOFF questionnaire. Health literacy was assessed with the HLS-EU-Q16 questionnaire. Sociodemographic information, including age, gender, social status and level of education, and subjective body image were obtained. χ 2 -tests of independence were calculated to determine the association between the investigated constructs.Results. Suspected eating disorders were more likely in female than male adolescents but were not related to gender in adults. Rates of suspected eating disorders increased with increasing age in adolescents and decreased with increasing age in adults. While levels of education were unrelated to suspected eating disorders, low social status was associated with higher rates of suspected eating disorders in adults but not adolescents. Inadequate or problematic health literacy and negative body image were associated with higher rates of suspected eating disorders compared to adequate health literacy and more positive body image.Discussion. Likely cases of eating disorders are related to health literacy and body image as well as sociodemographic factors. These constructs should therefore be addressed in future research to improve prevention programs.